Cobalt Oxide Nanoparticles Embedded in N‐Doped Porous Carbon as an Efficient Electrode for Supercapacitor. Issue 4 (4th April 2019) - Zhu, Maiyong; Chen, Qi; Kan, Jiarui; Tang, Jingjing; Wei, Wenjing; Lin, Jinkun; Li, Songjun
Abstract : Herein, a sequential pyrolysis and oxidation strategy is developed to prepare Co3 O4 nanoparticles embedded in N‐doped porous carbon (Co3 O4 @N‐pC) using a bimetal zeolitic imidazolate framework (ZIF‐67@ZIF‐8) as precursors, which is first obtained via a simple wet‐chemical process. The electrochemical performances of Co3 O4 @N‐pC, ZIF‐67@ZIF‐8 precursors, and Co@N‐Pc intermediates (the direct pyrolysis products from ZIF‐67@ZIF‐8) are studied as supercapacitor electrodes in comparison. The results reveal that the specific capacitance of the optimized Co3 O4 @N‐pC electrode can reach up to 422.8 F g −1 at 1 A g −1 with a good rate capability (256 F g −1 at 5 A g −1 ) and excellent long‐term cycling stability (87.9% retention after 5000 cycles). Such performance is superior over ZIF‐67@ZIF‐8 precursors (232 F g −1 at 1 A g −1, 168.9 F g −1 at 5 A g −1, and 82.7% retained after 5000 cycles) and Co@N‐pC intermediates (218.4 F g −1 at 1 A g −1, 171 F g −1 at 5 A g −1, and 76.3% retained after 5000 cycles). The findings in this work are expected to provide a new avenue to explore other metal oxide/carbon materials for various applications. Abstract : The bimetal zeolitic imidazole framework (ZIF‐67@ZIF‐8) is used as a precursor to prepare Co3 O4 nanoparticles embedded in N‐doped porous carbon (Co3 O4 @N‐pC), which exhibits superior electrochemical performance as a supercapacitor electrode.